Advances in Biomedical Sciences and Engineering - C Tjong, S. (Bentham Science Publishers, 2009)
This authoritative reference provides update information on the fundamental aspects and applications of biomaterials and biomedical sciences. It includes nickel-titanium alloys with superelasticity and shape memory effect, bioactive bone cement for orthopedic applications, and new research trends in polymer nanocomposites. This Ebook also describes the response of cells to ionizing radiation such as DNA damage responses in zebrafish. With chapters contributed by eminent scientists in the field of biophysics, biomaterials and biomedical engineering, this is a useful reference for graduate students, researchers and professionals in biomedical sciences and technologies.